Fort Wellington, Raffles Bay. - Historical Society of the Northern Territory ([Darwin] : Historical Society of the Northern Territory, 1971)
Account of expedition, Aug.-Sept. 1966, to Fort Wellington; includes historical notes on settlement and foundation, contact with natives of Iwaidja and Jacko tribes; Macassans known to have fished and traded in the area for many years.
Bibliography: p. 39-40.
Keywords: Northern Territory. Raffles Bay. Fort Wellington, 1827-1829.; Expedition to Fort Wellington, Northern Territory, 1966.; Defence - Military bases; Iwaidja / Yiwayja / Yiwadya people (N39) (NT SC53-13); Marrgu / Margu people (N45) (NT SC53-13); Fort Wellington (N.T.); Raffles Bay (N.T.) -- History; Australia, Northern -- Defenses -- History; Raffles Bay / Fort Wellington (West Arnhem Land NT SC53-13)